2004
DOI: 10.1097/01.ccm.0000145906.63859.1a
|View full text |Cite
|
Sign up to set email alerts
|

Use of blood products in sepsis: An evidence-based review

Abstract: In the absence of extenuating circumstances and following resolution of tissue hypoperfusion, red blood cell transfusion should be targeted to maintain hemoglobin at 7.0 g/dL or greater. Erythropoietin is not recommended as a specific treatment for sepsis-associated anemia. Fresh-frozen plasma should be given for documented deficiency of coagulation factors and in the presence of active bleeding or before surgical or invasive procedures. Antithrombin administration is not recommended. Specific platelet transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 59 publications
0
26
0
3
Order By: Relevance
“…However, correction of these abnormalities do not necessarily improve the outcomes in all the patients and unnecessarily exposes the child to the risks of blood product transfusions [26]. There are no studies to suggest that correction of more severe coagulation abnormalities benefits patients who are not bleeding.…”
Section: Blood Productsmentioning
confidence: 97%
“…However, correction of these abnormalities do not necessarily improve the outcomes in all the patients and unnecessarily exposes the child to the risks of blood product transfusions [26]. There are no studies to suggest that correction of more severe coagulation abnormalities benefits patients who are not bleeding.…”
Section: Blood Productsmentioning
confidence: 97%
“…En 2003, des experts internationaux en réanimation et maladies infectieuses ont développé des recommandations sur l'utilisation des produits sanguins dans le sepsis [27]. Pour la transfusion de plaquettes ces recommandations sont gradées E, notamment :…”
Section: Transfusion De Plaquettesunclassified
“…Approximately 40-50% of patients admitted to the ICU are transfused at least 1 RBC unit. Several studies have shown that RBC transfusion in sepsis did not improve oxygen delivery, oxygen consumption, mixed venous oxygen saturation or lactate levels [84][85][86].…”
Section: Clinical Evidence For Transfusion In Sepsismentioning
confidence: 99%